Romanesque Churches as Art-Objects: Methodology, Ways of Research, and Expected Results in Central Italy - Gigliozzi, Maria Teresa (Actual Problems of Theory and History of Art, 2017)
In the Middle Ages, architecture was considered to be one of the mechanical arts, and the role of medieval architects is still under debate. Thus, can a medieval church be seen as an art-object? Since the Renaissance,with the studies of architectural aesthetics, architectural works have been widely regarded as art works.Therefore, as an art-object it needs classification and the cognitive approach which take advantage of specific and constantly revised instruments.Art historians can contribute to architecture history by evaluating buildings as art-objects, not only reconstructing the chronological sequence of their artistic phases, but also aiming to understand their initial planning, function, space organization for liturgy, together with their religious, political and cultural significance. Moreover, the study of constructive techniques, materials, building strategies and models cannot be neglected.In the last twenty years, Italian and international historiography showed an attentive consideration and are newed interest in Romanesque matters, in particular in the origins of the Romanesque style itself (11th century).Several interesting projects have been launched arising from the necessity to rethink past categories and to present new cataloguing, based on scientifically rigorous research that includes innovative techniques and interdisciplinary coordination. Encounter and dialogue between the different disciplines — such as restoration, architectural survey and archaeology — is an imperative. As regards Central Italy, the research is in its very early stages. Historiography still records a few studies that take the phenomenon into consideration from a macro-territorial point of view. The topic proposed aims at focusing attention on the need for a new systematic categorization and reinterpretation of Romanesque architecture in Central Italy, by presenting some project guidelines: a synchronic analysis of monuments (like the cathedrals of the 11th century in Florence, Lucca and Pisa, in Tuscany; in Assisiand Spoleto, in Umbria; in Ancona in the Marche). This complex work, in the future, requires accurate analysis together with a conscious and in-depth overview.The thematic context of the boоk provides an appropriate place for dialogue and seeks input and adviceon this topic.
Keywords: architecture; Romanesque churches; archeology; landscape; Central Italy; methodology